ADMINISTRATIVE SERVICE OF A.F. REBROV IN THE CAUCASUS UNDER THECOMMAND OF GENERAL A. P. YERMOLOV - Olga Zaporozhtseva (Гуманитарные и юридические исследования)
The article analyzes the administrative activity of A. F. Rebrov under the head of the administration in the Astrakhan, Caucasus provinces and in the Republic of Georgia, A. P. Yermolov, in one of the difficult periods in the history of the Caucasus. Thanks to the knowledge of the peculiarities of the region land the life of peoples in the North Caucasus, it was possible to successfully fulfill the orders of the authorities. Among them was the compilation of "The review of the lands of the Caucasian province in relation to their properties, status and rank of the inhabitants inhabiting it". The document defined the boundaries of the Caucasian province, described the peoples living in the territory of the province; prepared the rules "for economic management in the production of buildings at the Caucasus Mineral Waters". All those who could build buildings on the allotted land for living or renting out for visitors during the holiday season on the CMW were involved. A. F. Rebrov studied not only the necessary information about the "economic condition of each regiment..." but also "drew up rules to allot land to Cossack troops" "observed the places with military authorities to settle the Cossacks at the new frontline". The author shows the national policy, which also required the necessary historical knowledge and diplomatic approach. He gained such experience while being in the Caucasus during the expeditions of his superiors as a secretary, so he was able to successfully fulfill the orders concerning the settlement of national interests with the Kabardian and Nogai peoples. After the resignation of A. P. Ermolov, Rebrov faithfully served the orders of appointed in 1827 commander of the troops in the Caucasus, and chief superintendent of the civil part and border affairs of the provinces of Astrakhan, the Caucasus, and in Georgia, the field-Marshal-General count I. F. Paskevich-Erivan For three years.